The characteristics of bovine satellite cells with highly scored genomic estimated breeding value - Jae Ho Han; Ji Suk Yu; Do Hyun Kim; Hyun Woo Choi (The Korean Society of Animal Reproduction and Biotechnology, 2023)
Background: The grading of Hanwoo (Korean native cattle) is based on four economic traits, and efforts have been continuously made to improve the genetic traits associated with these traits. There is a technology to predict the expected grade based on the 4 economic genetic SNP characteristics of Korean cattle calves using single nucleotide polymorphism (SNP) technology. Selection of highly proliferative, self-renewing, and differentiating satellite cells from cattle is a key technology in the cultured meat industry. Methods: We selected the Hanwoo with high and low-scored of genomic estimated breeding value (GEBV) by using the Hanwoo 50K SNP bead chip. We then isolated the bovine satellite cells from the chuck mass. We then conducted comparative analyses of cell proliferation, immunocytochemistry, qRT-PCR at short- and long-term culture. We also analyzed the differentiation capability at short term culture. Results: Our result showed that the proliferation was significantly high at High scored GEBV (Hs-GEBV) compared to Low scored GEBV (Ls-GEBV) at short- and long-term culture. The expression levels of Pax3 were significantly higher in Hs-GEBV bovine satellite cells at long-term culture. However, there were no significant differences in the expression levels of Pax7 between Hs- and Ls-GEBV bovine satellite cells at short- and long- term culture. The expression levels of MyoG and MyHC were significantly high at Ls-GEBV bovine satellite cells. Conclusions: Our results indicated that selection of bovine satellite cells by Hanwoo 50K SNP bead chip could be effective selection methods for massive producing of satellite cells.